Characterization of Pearl Millet Root Architecture and Anatomy Reveals Three Types of Lateral Roots - Passot, Sixtine; Gnacko, Fatoumata; Moukouanga, Daniel; Lucas, Mikaël; Guyomarc’h, Soazig; Ortega, Beatriz Moreno; Atkinson, Jonathan A.; Belko, Marème N.; Bennett, Malcolm J.; Gantet, Pascal; Wells, Darren M.; Guédon, Yann; et al. (Frontiers in Plant Science, 2016)
Pearl millet plays an important role for food security in arid regions of Africa and India. Nevertheless, it is considered an orphan crop as it lags far behind other cereals in terms of genetic improvement efforts. Breeding pearl millet varieties with improved root traits promises to deliver benefits in water and nutrient acquisition. Here, we characterize early pearl millet root system development using several different root phenotyping approaches that include rhizotrons and microCT. We report that early stage pearl millet root system development is characterized by a fast growing primary root that quickly colonizes deeper soil horizons. We also describe root anatomical studies that revealed 3 distinct types of lateral roots that form on both primary roots and crown roots. Finally, we detected significant variation for two root architectural traits, primary root lenght and lateral root density, in pearl millet inbred lines. This study provides the basis for subsequent genetic experiments to identify loci associated with interesting early root development traits in this important cereal.